Evolution of Capabilities in the Discovery Cycle of an Innovation in the Pharmaceutical Market - Da Veiga, Claudimar Pereira; Da Veiga, Cássia Rita Pereira; Giacomini, Mônica Maier; Kato, Heitor Takashi; Del Corso, Jansen Maia (International Review of Management and Marketing, 2015)
The objective of this study is to analyze the evolution of dynamic capabilities in the discovery cycle of an innovation in the pharmaceutical market of erectile dysfunction in the period of twenty years. To achieve this, two distinct and complementary concepts were applied: models of March (1991) to exploitative and explorative discovery in the organizational learning process and the three components of dynamic capabilities. The result showed that the components of the capabilities may be identified in the discovery cycle of Viagra®. The study confirms the existence of a stock of knowledge among the companies in the pharmaceutical market of erectile dysfunction as well as a large absorptive capacity among all of them. Keywords: Marketing; Innovation; Pharmaceutical industry; Property Intellectual. JEL Classifications: M1; M3; M19